A single-dose live-attenuated YF17D-vectored SARS-CoV-2 vaccine candidate - Lorena Sanchez‐Felipe; Thomas Vercruysse; Sapna Sharma; Ji Ma; Viktor Lemmens; Dominique Van Looveren; Mahadesh Prasad Arkalagud Javarappa; Robbert Boudewijns; Bert Malengier‐Devlies; Laurens Liesenborghs; Suzanne J. F. Kaptein; Carolien De Keyzer; et al. (2020)
The expanding pandemic of coronavirus disease 2019 (COVID-19) requires the development of safe, efficacious and fast-acting vaccines. Several vaccine platforms are being leveraged for a rapid emergency response1. Here we describe the development of a candidate vaccine (YF-S0) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that uses live-attenuated yellow fever 17D (YF17D) vaccine as a vector to express a noncleavable prefusion form of the SARS-CoV-2 spike antigen. We assess vaccine safety, immunogenicity and efficacy in several animal models. YF-S0 has an excellent safety profile and induces high levels of SARS-CoV-2 neutralizing antibodies in hamsters (Mesocricetus auratus), mice (Mus musculus) and cynomolgus macaques (Macaca fascicularis), and—concomitantly—protective immunity against yellow fever virus. Humoral immunity is complemented by a cellular immune response with favourable T helper 1 polarization, as profiled in mice. In a hamster model2 and in macaques, YF-S0 prevents infection with SARS-CoV-2. Moreover, a single dose conferred protection from lung disease in most of the vaccinated hamsters within as little as 10 days. Taken together, the quality of the immune responses triggered and the rapid kinetics by which protective immunity can be attained after a single dose warrant further development of this potent SARS-CoV-2 vaccine candidate. A candidate vaccine against SARS-CoV-2 that uses the yellow fever 17D live-virus vector is highly efficacious and displays a favourable safety profile in Syrian hamster, mouse and cynomolgus macaque models.